1982
DOI: 10.1007/bf00151147
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive phase of flares in soft X-ray emission

Abstract: Observations using the Bent Crystal Spectrometer instrument on the Solar Maximum Mission show that turbulence and blue-shifted motions are characteristic ofthe soft X-ray plasma during the impulsive phase &flares, and are coincident with the hard X-ray bursts observed by the Hard X-ray Burst Spectrometer. A method for analysing the Ca xIx and Fe xxv spectra characteristic of the impulsive phase is presented. Non-thermal widths and blue-shifted components in the spectral lines of Ca xlx and Fe xxv indicate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(125 citation statements)
references
References 14 publications
4
118
3
Order By: Relevance
“…First, the expected outflow of hot gas into the corona during the hard phase was detected with SMM (Antonucci et al 1982). Second, the properties of the H a emission in bright points in the impulsive phase agree well with those calculated in models (Bruevich 1995).…”
Section: Accelerated Particles In Impulsive Solar Flaressupporting
confidence: 78%
“…First, the expected outflow of hot gas into the corona during the hard phase was detected with SMM (Antonucci et al 1982). Second, the properties of the H a emission in bright points in the impulsive phase agree well with those calculated in models (Bruevich 1995).…”
Section: Accelerated Particles In Impulsive Solar Flaressupporting
confidence: 78%
“…At the onset, blue shifts of the order of 150 km s −1 to 300 km s −1 were also observed, occasionally even 500 km s −1 . Antonucci et al (1982) studied soft X-ray emission observed with SMM, and also found turbulent velocities of more than 100 km s −1 and upflows with speeds up to 400 km s −1 . Similar results were obtained from the Bragg Crystal Spectrometer (BCS) on Yohkoh (Mariska 1994).…”
Section: Flaresmentioning
confidence: 97%
“…Doschek et al 1979), the Solar Maximum Mission (SMM) X-ray polychromator (XRP) Bent Crystal Spectrometer (BCS) (cf. Antonucci et al 1982), and from the Bragg Crystal Spectrometer (BCS) on YOHKOH (see, e.g., Bentley et al 1994). The observations were mainly of Hand He-like lines (in particular Ca xix), which are formed over a very broad range of temperatures, 8-25 MK (1 MK = 1 × 10 6 K).…”
Section: Introductionmentioning
confidence: 99%